A recirculação de videoclipes interativos no youtube a partir da apropriação dos usuários - Santos, Fabrícia Kelly Guedes dos (2017)
Music video is considered the most opened audiovisual genre for experimentations. When it comes on television, around the 1980s on Music Television (MTV), this kind of format was recognized as a television product known for its inventiveness. With the technology development and the internet advent the music video exceeds its status of television product and gets potentiality in the circulation from the Web. The music video potentiates its innovative and experimental aspect right on the internet, transcending the digital media possibilities. In this digital ambience, the interactive music videos emerge, the audiovisual products that allow the user participation at any moment during the process of making its content. Companies develop platforms to support the interactive features, each video has its own website. The user make her/his video directly on the page, but s/he doesn?t have autonomy over the product circulation, the music video is restricted to the original platform. The provided interactivity refers to the possibilities of intervention by the user over the music video content, it doesn?t have interaction among users properly, the experience is personalized and individualized. However, we have observed that these users get the videos and share it on platforms that go beyond to the official website. This process shows our study object, the recirculation of interactive music videos on YouTube according to the users appropriation. With the purpose of assimilating this phenomenon, we have investigated the configuration of the music video since its origin until the introduction on cyberspace, also analysing the changes in production process, circulation and consumption from the participatory culture and the online sharing. By adopting the inductive method, we exemplify with the music videos “The wilderness downtown”, “Three dreams of black” and “All is not lost”, these being the corpus of our analysis. In the conclusions, we identify that those described platforms restrict the action from the users to interactions in a technicist way and through the recirculation of music videos on YouTube the user experience also permeates the sharing and the multiinteraction (PRIMO, 2008) among users.